2017
DOI: 10.1111/gwat.12589
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Streambed Heterogeneity and Anisotropy on Residence Time of Hyporheic Zone

Abstract: The hyporheic zone (HZ), which is the region beneath or alongside a streambed, plays an important role in the stream's ecology. The duration that a water molecule or a solute remains within the HZ, or residence time (RT), is one of the most common metrics used to evaluate the function of the HZ. The RT is greatly influenced by the streambed's hydraulic conductivity (K), which is intrinsically difficult to characterize due to its heterogeneity and anisotropy. Many laboratory and numerical studies of the HZ have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
(93 reference statements)
0
18
0
Order By: Relevance
“…Due to the particles' different starting positions, they rarely have the same RT, and thus, the mean and median RTs are two common indicators used to describe the performance of particles remaining in the HZ. Liu and Chui () found that the median RT was more stable than the mean RT among different stochastically generated cases, with consideration of heterogeneity and anisotropy of hydraulic conductivity. Therefore, in this study, median RT is used as the indicator to describe total reaction time in the HZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the particles' different starting positions, they rarely have the same RT, and thus, the mean and median RTs are two common indicators used to describe the performance of particles remaining in the HZ. Liu and Chui () found that the median RT was more stable than the mean RT among different stochastically generated cases, with consideration of heterogeneity and anisotropy of hydraulic conductivity. Therefore, in this study, median RT is used as the indicator to describe total reaction time in the HZ.…”
Section: Methodsmentioning
confidence: 99%
“…The hyporheic zone (HZ hereafter), which is the region beneath or alongside a streambed where active groundwater and surface water mix, plays an important role in the aquatic environment and stream ecology (Brunke & Gonser, ; Hester & Gooseff, ; Liu & Chui, ; Peralta‐Maraver, Reiss, & Robertson, ; Peterson, Sickbert, & Moore, ). The HZ forms a unique environment between surface water and groundwater for macroinvertebrates, and it is the locus of a number of important biogeochemical reactions; for these reasons, it is vital to the biological and ecological functioning of streams (Montgomery, Buffington, Peterson, Schuett‐Hames, & Quinn, ; Soulsby, Malcolm, & Youngson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Even short-term perturbations (e.g., flooding) can have long-lasting influences (Gomez-Velez et al, 2017). The shapes of RTDs in real dynamic river corridors can be very complex since RTDs are influenced by both subsurface physical features and hydrologic forcings (Boulton et al, 1998;Gomez & Wilson, 2013), including sediment permeability and porosity (Cardenas et al, 2004;Liu & Chui, 2018;Salehin et al, 2004), river morphology (e.g., riffles, bars, and dunes) (Buffington & Tonina, 2009;Cardenas, 2008;Cardenas & Wilson, 2007;Stonedahl et al, 2013), naturally occurring hydrologic processes and events (e.g., flooding, evapotranspiration, recharge, snowmelt and tidal cycles) (Gomez-Velez et al, 2017;Gomez-Velez & Wilson, 2013;Larsen et al, 2014), and anthropogenic activities (e.g., dam-induced stage fluctuations) (Shuai et al, 2019;Song et al, 2018). The dynamic hydrologic fluctuations can produce equivalently complex pathways and RTDs as complex geomorphic features (Schmadel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The dominating driver of HE is the variation of pressure along the streambed (Tonina and Buffington ), which is in turn induced by heterogeneities in hydraulic conductivity (Vaux ; Ward et al ; Herzog et al ; Liu and Chui ) and the interactions between surface water and streambed topography, such as dunes, steps, ripples, pool‐riffles, or flow obstacles (Tonina and Buffington ). Among the various morphological features, pool‐riffle sequences have received vast attention because they are ubiquitous (Buffington et al ) and may account for a large portion of HE in many streams (Harvey and Wagner ).…”
Section: Introductionmentioning
confidence: 99%